Private takings - Alessandro Marchesiani; Ed Nosal (Federal Reserve Bank of Chicago, 2014)
This paper examines the implications associated with a recent Supreme Court ruling, Kelo v. City of New London. Kelo can be interpreted as supporting eminent domain as a means of transferring property rights from one set of private agents - landowners - to another private agent - a developer. Under voluntary exchange, where the developer sequentially acquires property rights from landowners via bargaining, a holdout problem arises. Eminent domain gives all of the bargaining power to the developer and, as a result, eliminates the holdout problem. This is the benefit of Kelo. However, landowners lose all their bargaining power and, as a result, their property investments become more inefficient. This is the cost of Kelo. A policy of eminent domain increases social welfare compared to voluntary sequential exchange only when the holdout problem is severe, and this occurs only if the developer has very little bargaining power. We propose an alternative government policy that eliminates the holdout problem but does not affect the bargaining power of the various parties. This alternative policy strictly dominates a policy of eminent domain, which implies that eminent domain is an inefficient way to transfer property rights between private agents.
Keywords: 330